Credit constraints and the propagation of the Great Depression in Germany - Marc C. Adam; Walter Jansson (Freie Universität Berlin, School of Business & Economics, 2019)
We evaluate the role played by loan supply shocks in the decline of investment and industrial production during the Great Depression in Germany from 1927 to 1932. We identify loan supply shocks in the context of a time varying parameter vector autoregression with stochastic volatility. Our results indicate that credit constraints were a significant driver of industrial production between 1927 and 1932, supporting the view that a structurally weak banking sector was an important contributor to the German Great Depression. We find further that loan supply shocks were an important driver of investment in the early phase of the depression, between 1927 and 1929, but not between 1930 and 1932. We suggest possible explanations for this puzzle and directions for future research.
urn:nbn:de:kobv:188-refubium-25248-0
Keywords: C11; E32; N14; N24; 330; Bayesian; Credit supply; Great Depression; Germany